Diagnostic confusion caused by excess beta-carotene: a case of primary carotenemia - Harvinder K. Palaha; P.S. Meghana Priya; Preeti Puranik; Vindya S. Reddy; Arya Bhadran; Vinay K. Majjagi (MGM Journal of Medical Sciences)
Carotenemia is a benign condition characterized by yellow-orange skin discoloration, typically sparing the sclera, that results from excessive consumption of carotenoid-rich foods. Although it is benign, it is often misdiagnosed as jaundice, leading to unnecessary diagnostic procedures. We present a case of carotenemia arising from a high intake of carotene-rich foods.